2023
DOI: 10.1097/iae.0000000000003228
|View full text |Cite
|
Sign up to set email alerts
|

Wedge-Shaped Pars Plana Sclerotomies: Is It Still an Actuality in the Era of Microincision Vitrectomy?

Abstract: Purpose: To describe and evaluate the effectiveness of wedge-shaped sclerotomies to close 25-gauge and 23-gauge transconjunctival pars plana vitrectomies. Materials and Methods: This prospective, consecutive, interventional study examined 50 eyes of 50 patients who underwent 25-gauge and 23-gauge vitrectomy with wedge-shaped sclerotomies. Results: The number of eyes requiring a wedge shape for sclerotomy clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…In this context, scleral wound hydration, adhesive application, polyethylene glycol-based hydrogel bandage, and cauterization of sclerotomy sites aim to provide closure by changing the external scleral wound configuration, whereas techniques, such as wedge-shaped sclerotomies, scleral needling, and her-metic closure, aim to reconstruct the intrascleral architecture of sclerotomy. 12,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] The techniques in the first group seem to offer a reasonable closure but present some difficulties. In particular, the need to apply heat or light to polymerize thermally sensitive polymers, necessity of conjunctival dissection in some cases, and cost issues of bioadhesives can be counted among them.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this context, scleral wound hydration, adhesive application, polyethylene glycol-based hydrogel bandage, and cauterization of sclerotomy sites aim to provide closure by changing the external scleral wound configuration, whereas techniques, such as wedge-shaped sclerotomies, scleral needling, and her-metic closure, aim to reconstruct the intrascleral architecture of sclerotomy. 12,13,[16][17][18][19][20][21][22][23][24][25][26][27][28][29] The techniques in the first group seem to offer a reasonable closure but present some difficulties. In particular, the need to apply heat or light to polymerize thermally sensitive polymers, necessity of conjunctival dissection in some cases, and cost issues of bioadhesives can be counted among them.…”
Section: Discussionmentioning
confidence: 99%
“…Success rates with these perforating procedures, namely, wedge-shaped sclerotomies, scleral needling, hermetic closure, and refashioning of 23G sclerotomies, have been reported between 92% and 99.3%. 13,[17][18][19]29 It has been suggested that vitreous plug formation in the reconstructed sclerotomy or reversal of flow from the wound to the new opening induces sutureless closure. 13 Our NIS procedure is also related to the sclerotomy architecture and is comparable with the techniques outlined above for overall success and similarity of maneuvers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations